(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The long jump is an arena and field sport that is mostly dependent on maximal speed, explosive power, and speed power. The researchers employ novel aids in this performance, which is distinguished by a distinctive artistic performance that produces the dynamic style of this performance. This category additionally includes the creation of training techniques based on the use of aids and scientific methodologies during the training process because of the significance of this and the reduction in the digital level. Furthermore, there is a significant disparity between the numbers registered in the long jump event and the age group of young people. This decrease might be caused by a variety of factors, including physical frailty. As a result, the researchers turned to performance-based aids to assist jumpers in training in the appropriate direction and developing physical factors. The aim of this research was to increase junior long jumpers’ ability by preparing exercises with assistance. The researchers assumed that there were statistically significant variations in physical ability and accomplishment between the research samples before and post-tests. The research sample consisted of four (4) players from Baghdad governorate’s premier junior class. For the research sample, which numbers (4), the researchers employed the experimental approach and cardiac tests were performed on 1/7/2022. The training curriculum was developed and implemented over a period of eight weeks, following which post-tests were administered on March 9, 2022, and the findings of the study variables were determined.